Adverse childhood experiences (ACEs) and cardiovascular development from childhood to early adulthood: study protocol of the Niagara Longitudinal Heart Study - Terrance J Wade; Deborah D O’Leary; Kylie S Dempster; Adam J MacNeil; Danielle S Molnar; Jennifer McGrath; John Cairney (BMJ Open)
Introduction Recent reviews have found substantial links between a toxic childhood environment including child abuse and severe household dysfunction and adult cardiovascular disease (CVD). Collectively referred to as adverse childhood experiences (ACEs), this toxic environment is prevalent among children, with recent Canadian estimates of child abuse at 27%–32%, and severe household dysfunction at 49%. Based on these prevalence rates, the potential effect of ACEs on CVD is more significant than previously thought. Yet, how ACEs amplify the risk for later CVD remains unclear. Lifestyle risk factors only partially account for this connection, instead directing attention to the interaction between psychosocial factors and physiological mechanisms such as inflammation. The Niagara Longitudinal Heart Study (NLHS) examines how ACEs influence cardiovascular health (CVH) from childhood to early adulthood. Integrating the stress process and biological embedding models, this study examines how psychosocial and physiological factors in addition to lifestyle factors explain the relationship between ACEs and CVH.Methods This follow-up study combines three baseline studies from 2007 to 2012 that collected CVH measures including child blood pressure, heart rate, left ventricular structure and function, arterial stiffness indices and baroreflex sensitivity on 564 children. Baseline data also include anthropometric, biological, lifestyle, behavioural, and psychosocial measures that varied across primary studies. Now over 18 years of age, we will recruit and retest as many participants from the baseline studies as possible collecting data on ACEs, CVH, anthropometric, lifestyle and psychosocial measures as well as blood, saliva and hair for physiological biostress markers.Ethics and dissemination Ethics approval has been received for the NLHS follow-up. Written consent to participate in the follow-up study is obtained from each participant. Results testing all proposed hypotheses will be submitted for publication in peer-reviewed journals.